Kolaborasi Antara Kepala Sekolah, Guru, dan Siswa dalam Menciptakan Sistem Pendidikan yang Berkualitas - Ramdani, Zulmi; Amrullah, Silmi; Tae, Lidwina Felisima (MEDIAPSI, 2019)
The creation of education in accordance with the mandate of the law is a matter that must be built with the hard work and cooperation of all the important elements in Indonesia's national education system today. A good education system is created when the school is led by a competent and creative principal, as well as those who are able to foster good relationships with teachers at the school. In addition, teachers with appropriate personalities and competencies will support the creation of a good learning environment and encourage their students to actively perform and make them personal. This study aims to provide clear information about the importance of collaboration among elements of educational support. The study used a mixed case study methodology, an open questionnaire, and a descriptive statistical analysis of 173 subjects consisting of two principals, 43 teachers, and 130 students. The results of case studies explain how the role of principals is crucial in shaping the character and performance of schools, especially with regard to their leadership style and creativity. While the analysis of open questionnaires categorizes that students expect to become dream teachers are those who are able to become partners, those who have the competence, and those who are experienced. The role of the principal, the presence of a qualified teacher, and the similarity of students' perceptions to their school will result in a collaboration that is mutually supportive of one another.